Case Study: Antero-Posterior Projection of Pelvis Radiographic Examination Techniques in the Diagnosis of Hemiarthroplasty - Almira Dea Fattarizka; Hernastiti Sedya Utami (UM Purwokerto Press, 2021)
Hemiarthroplasty is a surgical procedure to replace half of the hip joint with a prosthesis or artificial joint. The radiology procedure for the Hemiarthroplasty at Orthopaedic Hospital Purwokerto uses Antero-posterior projection of the pelvis. This projection is different from the routine projection, namely the Unilateral Antero-posterior Hip Projection. The purpose of this study is to determine the procedure for radiographic examination in cases of Hemiarthroplasty and to find out the reasons for using the Antero-posterior Pelvis projection to establish the patient's diagnosis. This type of research was qualitative with a case study approach. Data collection conducted in December 2020 at the Radiology Installation of the Orthopaedic Hospital Purwokerto, using the methods of observation, documentation, and interviews with radiographers and radiologists. Data analysis performed with primary data taken from one patient with Hemiarthroplasty. The patient has a history of fracture (broken bone) in the right side of the femoral neck before hemiarthroplasty surgery. The results showed that the proper projection for Hemiarthroplasty is the Antero-posterior Pelvis projection. The reasons were to see a comparison between the right and left hip joints and to find if there is a space or distance from the hip joints after the surgery procedure. Radiologists can get needed anatomical information about the pelvis by performing an Antero-posterior projection.